AB0307 Predictive value of the baseline clinical, laboratory and echosonographic parameters of ra activity in progression of structural damage in dmards naÏve early ra patients – 6 months follow-up-. (12th June 2018) - Prodanovic, S.Z.; Colic, J.; Sefik-bukilica, M.; Radunovic, G.; Damjanov, N.
Abstract : Background: The structural damage of RA usually develops within the first two years of disease and the risk of joint destruction is still difficult to predict 1 Objectives: To assess predictive value of the clinical, laboratory and echosonographic parameters activity of early RA in progression of structural damage in DMARDs/glucocorticoid naïve patients in the first 6 months. Methods: Sixty-five pts. (56 females, mean age 53±14.1 years) with early RA (EULAR/ACR 2010 criteria) and symptoms duration of ≤1 years. (mean duration of 3.6 months) were included during the 2012–14 years. and followed up 6 months. Patients were DMARDs/glicocorticoid naïve and had no X-ray visible structural damage. The ESR, CRP, RF, ACPA and MMP3 were measured. DAS28 index was calculated. US assessment was performed blindly to patient's medical history, on the same day when early RA diagnosis was established and repeated after 6 months, using 18MHz linear probe by ESAOTE My Lab 70 machine. Presence of bone erosions and Power Doppler (PD) signal, were recorded at each hand's joint, as well as at MTP1–5 joints of both side, according to OMERACT US group definition. The semi quantitative method (0–3) was applied for assessing US synovitis and total Power Doppler joint score (TPDJs)/pts. was calculated. Results: Fifty-nine pts. had finding of US bone erosions at baseline visit and 62 pts had it after 6 months. The significant increase of bone erosions and significant decrease of TPDJs/pts were found after follow-up (2.2. vs. 3.1 respectively; 10. vs. 4.5 respectively; Wilcoxon test: p<0.001). There was no statistical significant difference between the groups of pts. with (42 pts.) and without (23 pts.) new (≥1) US bone erosion after 6 months regarding value of ESR (41. vs. 39; p=0.973), CRP (18. vs. 11; p=0.255), RF (82. vs. 114; p=0.652), ACPA (184. vs. 319; p=0.784) MMP3 (110. vs. 83; p=0.245), DAS28 (5.7. vs. 5.3; p=0.269), total number of bone erosions (2. vs. 2; p=0.06) and TPDJs/pts (10. vs. 12; p=0.831). Univariant logistic regression analysis showed significant predictive value for US bone erosions finding at baseline visit OR 0.68 (0.48–0.98), p=0.04 for progression of structural damage after 6 months of follow up but not for value of: ESR: OR 1.28 (0.45–3.61), p=0.635; CRP: OR 2.75 (0.95–7.93), p=0.06; RF: OR 0.83 (0.30–2.30), p=0.726; ACPA: OR 0.96 (0.33–2.78), p=0.904; MMP3: OR 1.28 (0.42–3.88), p=0.656; DAS28: OR 1.23 (0.82–1.86), p=0.311 and TPDJs/pts OR 0.98 (0.93–1.02), p=0.344. Conclusions: Initial finding of US bone erosion is the most important risk factor for progression of structural damage with our DMARDs/glucocorticoid naïve early RA patients in the first 6 months of disease duration. Reference: [1] Morel J, Combe B. How to predict prognosis in early rheumatoid arthritis. Best Pract Res Clin Rheumatol2005;19:137–46. Disclosure of Interest: None declared